Perspectives on treating hypertension in old age The burden of polypharmacy, risks of treatment and GPs' treatment probability - Streit, Sven (OPTIMA, 2018)
With increasing age, blood pressure rises as a consequence of arterial stiffness and it has been debated whether or not to it is beneficial to treat hypertension in old age especially in >75-year-olds when they have multimorbidity, polypharmacy or frailty. Large hypertension trials showed that lowering SBP in >60-year-olds is beneficial and lowers the risk for myocardial infarction, stroke and all-cause mortality, even in >80-year-olds. However, these trials lack generalizability and typically excluded multimorbid patients that are frail. At the same time, observational studies rose concerns about lowering SBP too much since there are several cohort studies showing a reverse association of low SBP and increased mortality and accelerated cognitive decline especially in >75-year-olds. However, current hypertension guidelines advise physicians to lower SBP to values of even <130mmHg in all patients from the age of 60 years, which fuelled the discussions about the benefits and harms of lowering SBP too much in >75-year-olds under antihypertensive treatment especially when they are frail defined as having low hand grip strength or complex health problems in multiple domains of daily living. The general aim of this thesis is to increase the scientific knowledge about the effects of treating hypertension in >75-year-olds with frailty. This thesis has three aims: 1) to measure the prevalence of polypharmacy in older patients; 2) to test for an association between low SBP and mortality, cognitive function, daily functioning, and QoL in older patients under antihypertensive treatment; and 3) to understand the role that frailty plays in GP decisions about treating hypertension in old age across countries and see if those differences can be explained by country-specific cardiovascular disease burden and life expectancy.